Development of Scaffolding in Stimulating Students Motivation and Language Acquisition - Talitha, Stella; Mahajani, Tri; Rosdiana, Rina (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
This study aims to get an overview of the implementation of scaffolding in student language acquisition and describe student motivation in participating in language acquisition activities with the use of scaffolding. Through the application of scaffolding, language acquisition is obtained by learners. This study uses qualitative descriptive research design because this study presents research results based on facts that exist in everyday life as they are. Language acquisition for students on the words steel tank, gondola, scour, rivers, paddled; wings, tail, antennae, beak, muzzle, ankles, as per teacher-designed scaffolding. Of the six stages of scaffolding, five stages are carried out by teachers, the last stage is reflective of students and teachers only. For the level of motivation and intelligence starting from the highest percentage of motivation based on intelligence: students who are intelligent and motivated as much as 54%, students have average intelligence and motivated 19% who are intelligent and unmotivated, 12%; Smart and unmotivated students and average and unmotivated students, 2% each. This indicates that in general, the use of scaffolding affects student motivation in language learning with the help of other activities programmed by the school.